THE LIVING QURAN: TRADISI FREE LUNCH SETELAH SHALAT JUMAT DI MASJID JOGOKARIYAN YOGYAKARTA - Wely Dozan; Saepul Rahman (REVELATIA: Jurnal Ilmu Al-Qur'`an dan Tafsir, 2021)
The study of living Qur'an is one of the studies in the form of scientific research on social events in the Muslim community by positioning the Qur'an as the main behavior and actions in daily life. From there, it will be seen how they react continuously and live up to the values ​​of the al-Qur'an in their community. The study of the Living Qur'an appears as a phenomenon of the Qur'an in everyday life, namely the function and meaning of the Qur'an is understood and practiced by the Muslim community in real terms in everyday life. Unlike the study of the Koran which only focuses on the al-Qur'an as an object of study that focuses on the textuality of the Qur'an it self, while the living Al-Qur'an is more focused on the way people position the Qur'an. In his daily life. One example of this living Qur'an practice is the tradition of Free Lunch after Friday prayers at the Jogokariyan Mosque. In this tradition, the Muslim community tries to live up to the value of sodaqoh contained in the Al-Qur'an surah al-Baqarah verse 261. This tradition emerged in the community as a form of social tradition with the aim of providing assistance in the form of free lunch (free lunch) to Friday congregation.